Decorative Alphabets and Initials - Alexander Nesbitt (USA Dover Publications, 1959)
A sourcebook of initials and ornamental letters reproduces designs from the eighth century to the present.
Keywords: Arts (3Gdafs; Alphabets; Initials; General